The Monumental Basin of Mont Beuvray and its Possible Orientation towards the Constellation of Gemini - Maumené, Claude (Journal of Skyscape Archaeology, 2019)
The Bibracte Basin, a Celtic monument in the centre of Bibracte, the capital of the Gallic Aedui people, remains an enigma (Almagro-Gorbea and Gran-Aymerich 1991c, 192), in that no other monumental basin of the same vesica pisces (naviform) shape is known to exist. It has been determined that its transversal axis is orientated towards the rising or the setting Sun at key dates of the Celtic year (Almagro-Gorbea and Gran-Aymerich 1991a, 158-159; White 1991, 275-277; García Quintela and César Gonzales-García 2016, 298), and the present study complements earlier studies of the solar character of the basin by focusing on how the main axis, whose importance has been ignored up to now, is orientated to a celestial alignment with the constellation of Gemini. Further, a correlation is observed between the precise orientation of the basin towards the star Castor and the etymology of "Bibracte", located on what is today known as Mont Beuvray. This is related to the religious importance of the Dioscuri in the Gallic pantheon.